Carbon storage potential and influencing factors of mangrove plantation in Kaozhouyang, Guangdong Province, South China - Kang, Li; Huamei, Huang; Ran, Yan; Shengpeng, Zhang; Di, Dong; Bo, Peng (Frontiers in Marine Science, 2025)
Mangrove plantation is a fundamental approach for sustainable management of tropical and subtropical coasts to capture and store atmospheric carbon. However, it is unknown whether the carbon accumulation potential of planted mangroves is as much as natural mangroves, and the effects of tree species, forest age and hydrodynamic conditions on carbon storage are still unclear. This study investigated the carbon storage potential and influencing factors for planted mangroves in the Kaozhouyang, Huidong County, GuangDong Province. The results showed that mangrove plantation significantly increased the carbon stock of vegetation and soil (vegetation carbon stock: 9.96 45.06 t C/ha, soil carbon stock: 70.37 110.64 t C/ha) compared with non-vegetation mudflat (63.73 t C/ha). However, the ecosystem carbon stock for planting sites was still lower than that of natural Avicennia marina (282.86 t C/ha), and the significantly difference were mainly reflected on soil carbon stock (P<0.05). Further results showed that the carbon accumulation was affected by forest age, tree species and tidal level. The vegetation biomass/carbon stock gradually increased with forest age (P<0.05), but the difference is not significant for soil carbon stock, which indicated that carbon accumulation is mainly concentrated on vegetation at the early stage of mangrove restoration. In addition, the suitable habitat conditions (landward) and the fast growing species (Sonneratia apetala) are more beneficial to carbon accumulation. Our results suggested that mangrove plantations can achieve carbon storage and sequestration in vegetation and soil for increasing carbon sinks with suitable species selection and management.